Factors contributing to termination of pregnancy amongst teenagers at Maggys Hope Clinic at Polokwane Municipality, Limpopo Province South Africa - Baloyi, K.L. (University of Limpopo, 2015)
Background: There are a high number of teenagers seeking Termination of Pregnancy (TOP) at Maggys Hope Clinic in Polokwane Municipality in Capricorn District in Limpopo Province after the Termination of Pregnancy Act was passed in 1997. The numbers have doubled since the inception of the Children's Act no 38 of 2005 and the Sexual Offences Bill in 2008. The report by Stats SA and Department of education also indicated that the numbers have also doubled. Objective: The aim of the study was to determine the factors contributing to termination of pregnancies amongst teenagers at Maggys Hope Clinic in Polokwane Municipality, Limpopo Province. Methods: An exploratory, descriptive qualitative research design was used to identify and describe the factors contributing to termination of pregnancies among teenagers in Maggys Hope Clinic in Capricorn district Limpopo Province South Africa, in April 2014. Results: The results of the study revealed that CTOP legislation is one of the reasons why teenagers terminate. All the twenty participants indicated age and marital status as the motivation as the contributing factor. Looking at the age and educational level the most pushing factor is that thirteen of the participants are still at school. Eleven of the participants have no knowledge of contraceptives. This is a serious concern. Participants indicated that they had very little knowledge on reproductive health issues. The rest of the pushing factors are parental pressure, contraceptive failure, fear of parental disappointment and unpreparedness to raise a child as well. Conclusion: It can thus be concluded that teenage termination of pregnancies is a major health concern in South Africa, Africa and globally. Teenagers’ health is in danger due to engaging in unprotected sex banking on TOP as a solution. The study found that age and fear from dropping out of school, lack parental involvement in sexual matters, family economic status and marital status, including lack of knowledge and information on reproductive health issues, were the main factors contributing to termination of pregnancies among teenagers in Maggys Hope Clinic in Capricorn District, Limpopo Province.
Thesis (MPH.) --University of Limpopo, 2015
Keywords: Pregnancy; Teenagers; Termination of pregnancy; 363.460968; Pregnancy,Unwanted --Limpopo; Teenage pregnancy -- South Africa; Abortion -- South Africa